The intratumoral microbiota heterogenicity is related to the prognosis and tumorigenesis of cervical cancer - Guo, Yi; Xiao, Yuhang; Zhang, Changyi; Wang, Ying; Cao, Guangxu; Tse, Ka Yu; Han, Zhiqiang; Li, Fang; Zhi, Yong (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe intratumoral microbe-host interaction plays crucial role in the development of cancer. The microbiome can influence cancer development by modulating inflammation, immune responses and metabolic pathways. Therefore, we aim to delineate the landscape and role of intratumoral microbiota in cervical cancer (CC).MethodsThe presence of bacterial community in CC tissues was confirmed by fluorescence in situ hybridization (FISH). Then 16s rRNA and RNA-Seq were used to characterize the composition of intratumoral microbiota. Combined with cervical squamous cell carcinoma (CESC) data from the Tumor Cancer Genome Atlas (TCGA), the clinical signatures of intratumoral microbiota and DEGs were further analyzed. Finally, the effect of the up-regulated Fibrinogen beta chain (FGB) expressed fragment peptide on the biological behavior of cancer was verified in vitro.ResultsWe found the composition heterogeneity of bacteria in CC tumors. Pseudomonas was most highly enriched in CC tissues and grouped according to the relative abundance level. The clinical characteristics of patients with relatively high abundance of Pseudomonas had the higher levels of fibrinogen and lower levels of white blood cell (WBC) and albumin (ALB) expression. Combining transcriptome data from the two our collective CC and TCGA-CESC cohorts, we found that Pseudomonas abundance was significantly associated with fibrinogen beta peptide expression and worse overall survival in CC patients. In vitro experiment revealed that Pseudomonas could promote the proliferation and migration of cervical cancer cells through overexpression of FGB.ConclusionsWe characterized the composition of the intratumoral microbiota in CC tissues and identified the most significantly differentially abundant bacteria between cancerous and non-cancerous tissues. Our findings provide novel insights into the relationship between intratumoral Pseudomonas and the tumorigenesis of CC. A deeper understanding of the tumor microenvironment and its associated microbiota may reveal new potential therapeutic targets and improve clinical outcomes.